MushPEC: Correcting Post-entrapment Processes Affecting Melt Inclusions Hosted in Olivine Antecrysts - Brahm, Raimundo; Zellmer, Georg F.; Kuritani, Takeshi; Coulthard, Daniel; Nakagawa, Mitsuhiro; Sakamoto, Naoya; Yurimoto, Hisayoshi; Sato, Eiichi (Frontiers in Earth Science, 2021)
Olivine-hosted melt inclusions (MIs) are widely used as a tool to study the early stages of magmatic evolution. There are a series of processes after MI trapping that affect MI composition, including post-entrapment crystallization (PEC) of the host mineral at the MI boundaries, exsolution of volatile phases into a “shrinkage bubble” and diffusive exchange between the MI and its host. Classical correction schemes applied to olivine-hosted MIs include PEC correction through addition of olivine back to the melt until it reaches equilibrium with the host composition and “Fe-loss” correction due to Fe-Mg diffusive exchange. These corrections rely on the assumption that the original host composition is preserved. However, for many volcanic samples the crystal cargo is thought to be antecrystic, and the olivine composition may thus have been completely re-equilibrated during long crystal storage times. Here, we develop a novel MI correction scheme that is applicable when the original host crystal composition has not been preserved and the initial MI composition variability can be represented by a simple fractional crystallization (FC). The new scheme allows correction of MI compositions from antecrystic hosts with long and varied temperature histories. The correction fits a set of MI compositions to modelled liquid lines of descent generated by FC. A MATLAB® script (called MushPEC) iterates FC simulations using the rhyolite-MELTS algorithm. In addition to obtaining the corrected MI compositions, the application of this methodology provides estimations of magmatic conditions during MI entrapment. A set of MIs hosted in olivine crystals of homogeneous composition (Fo77-78) from a basaltic tephra of Akita-Komagatake volcano was used to test the methodology. The tephra sample shows evidence of re-equilibration of the melt inclusions to a narrow Mg# range equivalent to the carrier melt composition. The correction shows that olivine hosts were stored in the upper crust ( c. 125– 150 MPa) at H2O undersaturated contents of c. 1 – 2 wt% H2O).